Effects of Workload Job Demand and Ineffective Leadership on Offshore Employee Well-being in Oil and Gas Industry: The Mediating Role of Friend Support - Abdul Wahab, M Wazien Afifi; Albert Gisip, Imelda; Syed Annuar, Sharifah Nurafizah (Journal of Social Transformation and Regional Development, 2021)
The aim of this study is to examine effects of workload job demand and ineffective leadership to the offshore employee well-being in oil and gas industry. In addition, this study also seeks to determine the mediating role of friend support to the relationships of workload job demand and ineffective leadership with offshore employee well-being. This paper is mainly based on secondary sources of information, through references and review of articles in selected journals pertaining to workload job demand, ineffective leadership and employee well-being in oil and gas industry. This paper highlights past studies on the effects of workload job demand and ineffective leadership to the offshore employee well-being. The reviews also address the related gaps from previous studies. This research paper is based on original research which seeks to contribute new knowledge and new approaches to solving existing problems by adapting and testing the mediating effects of friend support to the relationships between workload job demand and ineffective leadership with employee well-being particularly in the oil and gas industry.